ANTIOXIDANT ACTIVITY TEST OF ETHANOL EXTRACT OF BANGLE RHIZOME (ZINGIBER CASSUMUNAR ROXB) USING ABTS METHOD [2,2-AZINOBIS (3-ETHYLBENZOTHIAZOLINE)-6-SULFONIC ACID] - Muhammad Natsir Djide; Fhahri Mubarak; Rikayani Natasya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2022)
Antioxidants are compounds that can inhibit or prevent damage caused by free radical oxidation. Bangle rhizome (Zingiber cassumunar Roxb.) contains polyphenolic compounds which have antioxidant activity. This study aims to determine the antioxidant activity of bangle rhizome extract in reducing ABTS radicals [2,2'-azino-bis-(3-ethylbenzothiazoline)-6-sulphonic acid]. Bangle rhizome was macerated with 96% ethanol. The extract identified flavonoid and tested for antioxidant activity using the ABTS method with comparison quercetin. The results of the antioxidant activity test of bangle rhizome had an IC50 value of 25.320 ppm which was classified as very strong antioxidant, while the positive control of quercetin obtained an IC50 value of 3.394 ppm which was included in the very strong category. Bangle rhizome extract has very strong antioxidant activity in reducing free radicals.